Management of Pulmonary Embolism with Rheolytic Thrombectomy - Lisa Ferrigno; Robert Bloch; Judson Threlkeld; Thomas Demlow; Raman Kansal; Riyad Karmy-Jones (Canadian Respiratory Journal, 2011)
BACKGROUND: Catheter thrombectomy combining thrombus destruction with local thrombolysis has been used in patients with pulmonary embolism (PE) who are unstable or have significant right heart dysfunction, but have contraindications to systemic thrombolytic therapy.